How front-of-package labels, perceived food quality, brand loyalty, and consumer consciousness of nutritional value drive consumer satisfaction - Muhammad Moazzam; Haiqa Javed; Muhammad Mustafa Raziq; Muhammad Adnan Waseem; Muhammad Kamran Khalid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
Food labeling standards play a vital role in shaping our food choices. Many food-borne diseases can be effectively curtailed by adopting customer centered Front-of-Package (FOP) food labeling and nutritional standards. Past studies primarily cover consumer behavior towards food labels, yet there is a noticeable lack of literature underscoring factors affecting the consumer satisfaction towards FOP food labeling standards. To address this research gap, this study proposes an analytical framework to, first, analyze the impact of FOP food labeling standards on consumer satisfaction, second, examine the mediating role of perceived food quality and brand loyalty and third, test the moderating effect of consumer consciousness of nutritional value. A cross-section of 775 Pakistani consumers between the age of 18-65 years was drawn through purposive sampling technique and accessed through online survey to collect data. Data was analyzed using SmartPLS for structural equation modeling and confirmatory factor analysis to assess the effect size between variables. A significant positive association was found between FOP food labeling standards and consumer satisfaction, and perceived food quality and brand loyalty mediated this relationship. It was further established that consumer consciousness of nutritional value acts as a moderator in the association between FOP food labeling standards and perceived food quality and brand loyalty, respectively. In the light of these findings this study offers policy measures to enhance informed consumer choices and promote healthier eating habits. This paper fulfills an identified need to highlight inherent factors affecting consumer behavior towards FOP food labeling standards.
Keywords: 330; Front-of-package food labels; brand loyalty; perceived food quality; nutritionalawareness; consumer satisfaction